Who Gets Included in Community Supported Agriculture? Governance Design, Transaction Costs, and Socio-Demographic Patterns among Small Organic Farmers in Indonesia - Rahmatika, Maula Fadhilata; Mulyaningsih, Sri; Ulayya, Amira Hasnanuha (International Journal of Emerging Research and Review, 2026)
Objective: This study aims to examine how Community Supported Agriculture (CSA) governance design shapes the socio-demographic inclusion of small organic farmers. While CSA has gained attention as an alternative agri-food system, existing research remains predominantly consumer-oriented and provides limited explanation of how different categories of farmers are included or excluded. This study addresses this gap by reframing farmer participation as an institutional outcome rather than an individual choice. Method: The study adopts a qualitative comparative case study approach, focusing on two contrasting CSA models in Mojokerto, Indonesia. Data were collected through in-depth interviews with 38 farmers, CSA managers, and coordinators, complemented by document analysis and field observations. Guided by Transaction Cost Economics (TCE), qualitative data were analyzed using Atlas.ti through a deductive–inductive thematic analysis followed by cross-case comparison. Results: The findings show that CSA governance design plays a decisive role in shaping farmer inclusion. Decentralized, community-based governance relies on peer coordination and informal monitoring, effectively favoring experienced, land-owning farmers with strong social embeddedness. In contrast, centralized, organization-led governance internalizes coordination, monitoring, and certification costs, lowering entry barriers for younger, landless, or less experienced farmers, albeit with reduced autonomy. Socio-demographic characteristics thus emerge as reflections of governance compatibility rather than direct determinants of participation.  Novelty: This study contributes to CSA scholarship by conceptualizing farmer inclusion as an institutional outcome shaped by transaction cost allocation. By extending Transaction Cost Economics to alternative agri-food networks, it provides a governance-based explanation of inclusion and exclusion dynamics in CSA, particularly in developing-country contexts.